2021
DOI: 10.1007/s10557-021-07226-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Reperfusion in Patients with Transient ST-Elevation Myocardial Infarction—Prevalence, Importance and Approaches to Management

Abstract: Patients with transient ST-elevation myocardial infarction (STEMI) or spontaneous resolution (SpR) of the ST-segment elevation on electrocardiogram could potentially represent a unique group of patients posing a therapeutic management dilemma. In this review, we discuss the potential mechanisms underlying SpR, its relation to clinical outcomes and the proposed management options for patients with transient STEMI with a focus on immediate versus early percutaneous coronary intervention. We performed a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Since an earlier review of this topic [7], several articles concerning spontaneous reperfusion in the setting of STEMI have been published reinforcing the previous evidence base that patients with spontaneous reperfusion have more favorable outcomes compared to those without spontaneous reperfusion [6,[17][18][19][20]. A summary of these studies reporting clinical outcomes with t-STEMI is shown in Table 1.…”
Section: Transient Stemi and Clinical Outcomesmentioning
confidence: 86%
See 1 more Smart Citation
“…Since an earlier review of this topic [7], several articles concerning spontaneous reperfusion in the setting of STEMI have been published reinforcing the previous evidence base that patients with spontaneous reperfusion have more favorable outcomes compared to those without spontaneous reperfusion [6,[17][18][19][20]. A summary of these studies reporting clinical outcomes with t-STEMI is shown in Table 1.…”
Section: Transient Stemi and Clinical Outcomesmentioning
confidence: 86%
“…There is a substantial amount of evidence that patients with spontaneous reperfusion have smaller myocardial infarcts and better clinical outcomes than those patients without spontaneous reperfusion [7]. Understanding the mechanisms underlying spontaneous reperfusion is, therefore, important since this may identify possible novel therapeutic targets to improve outcomes in patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…While our case required immediate PCI to restore coronary perfusion, the patient described by Kok et al experienced spontaneous reperfusion and had no additional interventions performed prior to CABG. The major risk of patients managed with delayed PCI or CABG following spontaneous reperfusion is that of reinfarction, which, although reportedly rare, 31,32 was likely the source of VSR in the case reported by Kok et al Regardless, these two cases collectively emphasize the risks of VSR following incomplete or delayed reperfusion, the patient‐specific factors when considering optimal timing of repair, and the utility of ECMO in perioperative management.…”
Section: Discussionmentioning
confidence: 99%